If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-4) = 6(x + -1) Multiply -1 * -4 y + 4 = 6(x + -1) Reorder the terms: 4 + y = 6(x + -1) Reorder the terms: 4 + y = 6(-1 + x) 4 + y = (-1 * 6 + x * 6) 4 + y = (-6 + 6x) Solving 4 + y = -6 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = -6 + -4 + 6x Combine like terms: 4 + -4 = 0 0 + y = -6 + -4 + 6x y = -6 + -4 + 6x Combine like terms: -6 + -4 = -10 y = -10 + 6x Simplifying y = -10 + 6x
| 11a+8=85 | | 8x+8=10x+4 | | 9z+2=z+42 | | 3/6x=5 | | 3p+4m+2p= | | -25x^3y^2/-5x^2y^4 | | 6/9=8n/5 | | 1/18c=-13 | | x^2-(k+1)x+k=0 | | 2log(x-3)-logx= | | 8x+3x=3x+33 | | 10a-4.3=4x+4.7 | | 14-2v=8 | | 5x+3(4x-5)=15 | | 1000*t=7.4315 | | h=0.5+2 | | x^3-1/63 | | 1/b=-8 | | -c+3c+6d-8d-2+5= | | 7*(3x)=14*(x+2) | | 5(2-3)=25 | | 3e^2-2e-8=0 | | C=1000+75 | | -2=-2+6v | | x^3-x^2*y=363 | | 2x-74-6x=34 | | 1/2(7x-6)=x-10 | | 6ln(x+9)-7lnx= | | p/s=20 | | 4x^2+12x+9=5 | | 9t-7=t+25 | | 5x-2/3 |